The Study Of Instant Catfish (Pangasius Hypophthalmus) Protein Consentrate Sago Noodles Fortified With Spinach (Amaranthus Sp) Flour - Harsul Lisan; Dewita '; Syahrul ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted at the laboratory of Fish Processing Technology, Faculty of Fisheries and Marine Science, University of Riau, on July to August 2013. The research was intended to evaluate the effect of spinach flour fortification on nutritional value of instant catfish protein consentrate sago noodles. Four types of instant sago noodles were made from a mixture of sago (52,63%), catfish protein consentrate (7,89%) and water (39,47%) and the mixture was fortified with spinach flour at a level of 0%, 5%, 10% and 15% counted from sago flour weight. The result showed that instant sago noodles which fortified with 5% spinach flour was the most acceptable. Moisture of instant sago noodles fortified with 0%, 5%, 10% and 15% spinach flour was 11,43%, 9,55%, 9,27%, 7,35% respectively; fiber was 1,88%, 2,29%, 4,30%, 5,16% respectively; ash was 0,80%, 1,32%, 4,70%, 7,07% respectively; calsium was 68,82%, 118,96%, 206,52%, 289,90% respectively; vitamin A was <0,5 IU, <0,5 IU, <0,5 IU respectively and total bacterial count was 12,36 x 105 sel/g, 11,51 x 105 sel/g, 10,80 x 105 sel/g, 7,48 x 105 sel/g respectively.Keywords: Sago flour, spinach flour, catfish protein consentrate, instant sago noodles.